(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
In oral fissure, “squamous cell carcinoma (SCC) “is the commonest oral carcinomas which comprises (90- 95%). After the 5th decade of age, male predilection is double as compared to females. (40%)of OSCC are confined to the dorsal or ventral surface ofthe tongue,(thirty percent)on the floor of the oral fissure. “OSCC” regularly distresses maxillary and mandibular attached gingiva, buccal mucosa, retro-molarand palatal region. In 5 years’ survival percentage series from 20% OSCC in the floor of the mouth to 60% OSCC in alveolus portion of jawbone depicting poor prognosis. Although it is tough but it is required to do imaging studies to understand the results at the initialphases of the disease. Various modalities include conventional plain film radiography, panoramic radiograph, cone beam computed tomography,Perfusion computed tomography,Magnetic resonance imaging–(diffusion-weighted MRI, dynamic contrast-enhanced MRI), ultrasonography, single-photon emission computed tomography, fusion techniques such as (ECT/ CT, CT/MRI, PET/CT, PET/MRI) along with nuclear medicines – (2-deoxy-2-[18F] fluoro-D-glucose), (18F-FDG), 18F-3-fluoroalpha-methyltyrosine, (18F-FAMT) and L-1-[11C]-tyrosine(C-tyrosine), radionuclide imaging. These various imaging diagnostic modalities support in the grading of the tumor, valuation of the vascular supply, resolution about metastasis combined with confined lymph nodes as well as detached organs. Furthermore, imaging lessons help to forecast the possibility of resection and advance management, graft establishment, and diversity amongst reactive and metastatic lymph nodes,and amongst diseases reappearance and marks or adversative reactions of post-operation or emission therapy